A novel assay for serum creatinine using a creatine kinase cycling reaction. Issue 5 (25th February 2021) - Ueda, Shigeru; Sakasegawa, Shin-ichi
ABSTRACT: For assaying serum creatinine, the enzymatic method is regarded as accurate. However, a reliable measurement of low levels is problematic. We have developed a new method that utilizes an enzymatic cycling reaction involving creatine kinase (CK) in the presence of excess ATP and IDP and implicated the application to a serum creatinine assay by incorporating with creatininase. Here, we evaluated applying the CK cycling method to a serum creatinine assay. In this study, we focused on assessing whether an accurate measurement could be achieved, especially in the reference interval and the lower concentration range. The effective sensitivity of the assay using 30 U/mL CK was approximately 4-fold greater than that of a commercial reagent. Under these conditions, 0.19 mg/dL of creatinine was accurately detected. The correlation coefficient of the comparison study with an existing commercial reagent was 0.995. Moreover, the effect of the increased signal intensity on accuracy and precision was assured. Graphical Abstract: